Celiac Disease and Associated Autoimmune Conditions - Romano, Ana Sofia Cruz Afonso (2023)
Introduction: Celiac disease (CD) is a chronic, immune-mediated enteropathy that has been increasingly associated with other autoimmune conditions. The aim of this work was to review which autoimmune disorders have been associated with CD, highlighting the strength and clinical impact of that associations. Methods: Review of the published literature in PubMed between 2002 and 2023. Systematic reviews, meta-analysis, case-control and cohort studies were preferred for analysis. Results: CD has relevant associations with type 1 diabetes mellitus, autoimmune thyroid disorders (in particular, Hashimoto’s thyroiditis), systemic lupus erythematosus, arthritis rheumatoid, autoimmune hepatitis, primary biliary cholangitis, Crohn’s disease, ulcerative colitis, microscopic colitis, IgA nephropathy and psoriasis. Other autoimmune diseases such as autoimmune gastritis, Addison’s disease, Sjogren’s syndrome and non-infectious uveitis have been described as being potentially associated with CD, but the available data is weak to assume a relevant association. Conclusion: This review confirms that CD has important associations with others autoimmune diseases. Physicians who manage patients with CD or with any other abovedescribed autoimmune condition must be aware of that possible coexistence. This knowledge will allow early diagnosis and treatment of patients with concomitant diseases and the improvement of outcomes.